Surgical Approaches to Infra Orbital RIM Fractures: A Review Literature (Indian Journal of Public Health Research & Development, 2020)
In most people, the relationship between the ocular globes and the cheek tissues is such that on lateral view,the cheek projects beyond the eye. This relationship is primarily due to the development of the facial bonesbeneath the cheek tissues, fractures of the infra orbital rims causes severe deformity to the face with ocularimbalance, so infra orbital rim is essential to maintain the anatomy of the eye and shape of the eye.
Keywords: Infra orbital rim, diplopia, retro bulbar haemorrhage, sub conjunctival incision